(untitled) (Al-Academy, 2020)
The pioneers in the Iraqi theatre were of a great significance in the production of the theatre shows associated with social and political problems, which necessitated a kind of directing that contributed in installing the sociological pillar of the Iraqi theatre, where these shows were close to the traditional realistic shows some of which is soaked with simple symbolism. That could have given it some traits and characteristics which enabled these connotations to determine the type of the theatrical show and the forms of the direction advances according the adopted style by each theatre director, which forms a clear phenomenon in dealing with the ground of the Iraqi social reality and its reflection on the text and the show. The Iraqi theatre presented a number of these works such as (the flood- Knitting machine- I am your mother, oh Shakir- the palm tree- the neighbors- Al-Mutanabi) and many other works. That has been clear through the dramatic event and the characters construction until it has become evident feature in the Iraqi theatre show. In view of what has been mentioned, the movement of the young playwrights left this directing orientation and the local text characterized by realism to shows upon which the contemporary or modernistic style in the treatment of the sociology of the Iraqi society has been imposed, when they were presented in new theatre forms that imitate the modern reality and some of them used the popular proverbs in some sentences through some popular vocabulary items that affirms the presence of the sociological side in the theatre show. Thus, there have become two evident differences between the movement of the pioneers’ theatre and the new young generation, therefore the researcher formed the title of the study (sociology of the pioneers’ theatre show and the experiences of contemporary youths). The researcher determined her scientific directions in the research methodological framework which consists of the research problem and the need for it, in the following question: what is the sociology of the show in the pioneers’ theatre and the experiences of the youth’s theatre?The research importance and objective were (identifying the sociology of the show of the pioneers’ theatre and the experiences of the contemporary youths) and its spatial, temporal, and objective limits in addition to defining the terms (the sociology). The theoretical framework consists of two sections: the first section: the sociological features of the show in the pioneers’ theatre. The second section: the implications of the sociological structures in the experiences of the youth theatre. The procedural framework consists of the research community, methodology and tools, in addition the choice of the sample and analysis. The research samples consist of the following shows:1- Play – In the heights of love: written by: Falah Shakir and directed by: Fadhil Khalil2- Play – Gate number seven: written by: awatif Naeem and directed by : Sinan Al-Azawi The research ends with the results, discussion, conclusions and a list of resources.